Study on the bond behavior between steel bar with different derusting methods and concrete. (15th May 2022) - Feng, Haibao; Shang, Huaishuai; Yang, Jiaxing; Hu, Bin; Zhao, Weiyue
Abstract: In this paper, three different derusting methods: angle grinder, rust remover and shot blasting machine were selected to remove the corrosion products on the surface of steel bars with different corrosion ratios. The bond behavior between steel bars and concrete after different derusting methods was experimentally studied. To carry out this study, deformed steel bars with diameters of 14 mm, 18 mm, 22 mm and 25 mm were selected to conduct corrosion in the natural environment and 36 center-pulled specimens were cast. The following contents were studied during the test: (1) the weakening of the surface rib height of steel bar after various derusting methods; (2) the effects of derusting methods, corrosion ratio and steel bar diameter on the bond strength and peak slip were studied, the influence mechanism of various factors on the bond performance of specimens was revealed, and the influence law of various factors on the bond performance of specimens was summarized; (3) the bond-slip constitutive relation between steel bar and concrete with different diameters after different derusting methods were studied. Highlights: Three different derusting methods: angle grinder, rust remover and shot blasting machine were selected to remove the corrosion products on the surface of corroded reinforcement bars. The bond behavior between reinforcement and concrete after different rust removal methods is experimentally studied. The effects of derusting methods, corrosion rate and reinforcement bar diameter on the bond strength and peak slip were studied, the influence mechanism of various factors on the bond performance of specimens was revealed.